2017
DOI: 10.1016/j.sjbs.2016.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of white rot disease on beans caused by Sclerotinia sclerotiorum using Contans® and reduced fungicides application

Abstract: This study was conducted to determine the compatibility of Contans® () with fungicides against . Results showed that both Contans® and Topsin® significantly reduced the disease incidence caused by by 90% and 95% survival plants, respectively when they were individually applied and compared to control. While, soil application of Contans® and Sumisclex mixture was the most effective in suppressing the white rot disease incidence that produced 100% survival plants, application of combined with the reduced doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The treatment with the fungicide (Vitavax) showed the best results in reducing disease incidence and severity (6.67±1.18 and 0.88±0.08, respectively). Similar results were obtained by Elsheshtawi et al (2017) who reported that the "Topsin" fungicide significantly reduced the disease incidence caused by S. sclerotiorum by 90% and 95% survival plants, respectively.…”
Section: Pot Experimentssupporting
confidence: 88%
See 1 more Smart Citation
“…The treatment with the fungicide (Vitavax) showed the best results in reducing disease incidence and severity (6.67±1.18 and 0.88±0.08, respectively). Similar results were obtained by Elsheshtawi et al (2017) who reported that the "Topsin" fungicide significantly reduced the disease incidence caused by S. sclerotiorum by 90% and 95% survival plants, respectively.…”
Section: Pot Experimentssupporting
confidence: 88%
“…Isolates were purified and identified according to their morphological and microscopical characteristics as Sclerotinia sclerotiorum. This fungus was previously reported to be associated with bean white rot diseases (Khalequzzaman and Hossain, 2008;Aysan andDemir, 2009 andElsheshtawi et al, 2017).…”
Section: Isolation and Identification Of The Causal Organismsmentioning
confidence: 87%
“…Given this, the application of chemical fungicides, such as picoxystrobin (Aproach ® ) and boscalid (Endura ® ), is the standard procedure used for the control of SSR [26,27]. Fungal biological controllers, such as Trichoderma asperelloides, Trichoderma harzianum, and Coniothyrium minitans e.g., [28][29][30], have been considered to be a viable alternative for the treatment of soybean seed, although alterations in the water potential of the soil may limit the use of these fungi for biocontrol [31]. Even so, the ongoing advances in the development of new microbial strains with potential for biological control provide increasing hope for the discovery of new, as yet untested strains that are more effective for the suppression of Sclerotinia.…”
Section: Introductionmentioning
confidence: 99%
“…and produce antifungal substances that inhibit host growth [5,[7][8][9][10][11][12][13]. C. minitans can successfully control crop diseases caused by S. sclerotiorum in the field [14][15][16]. C. minitans destroyed the sclerotia, blocked the germination of apothecia by approximately 90% and reduced disease incidence in a bean crop by 50% [5,17].…”
Section: Introductionmentioning
confidence: 99%